Controlling states of water droplets on nanostructured surfaces by design. Issue 46 (6th November 2017) - Zhu, Chongqin; Gao, Yurui; Huang, Yingying; Li, Hui; Meng, Sheng; Francisco, Joseph S.; Zeng, Xiao Cheng
Abstract : The transition between the Cassie and Wenzel states can be controlled via precisely designed trapezoidal nanostructures on the surface, for which the base angle of the trapezoids and the intrinsic contact angle of the surface are two possible adjustable parameters. Abstract : Surfaces that exhibit both superhydrophobic and superoleophobic properties have recently been demonstrated. Specifically, remarkable designs based on overhanging/inverse-trapezoidal microstructures enable water droplets to contact these surfaces only at the tips of the micro-pillars, in a state known as the Cassie state. However, the Cassie state may transition into the undesirable Wenzel state under certain conditions. Herein, we show from large-scale molecular dynamics simulations that the transition between the Cassie and Wenzel states can be controlled via precisely designed trapezoidal nanostructures on a surface. Both the base angle of the trapezoids and the intrinsic contact angle of the surface can be exploited to control the transition. For a given base angle, three regimes can be achieved: the Wenzel regime, in which water droplets can exist only in the Wenzel state when the intrinsic contact angle is less than a certain critical value; the Cassie regime, in which water droplets can exist only in the Cassie state when the intrinsic contact angle is greater than another critical value; and the bistable Wenzel–Cassie regime, in which both the Wenzel and Cassie states can exist when the intrinsic contact angle is between the two critical values. A strong base-angle dependence of the first critical value is revealed, whereas the second critical value shows much less dependence on the base angle. The stability of the Cassie state for various base angles (and intrinsic contact angles) is quantitatively evaluated by computing the free-energy barrier for the Cassie-to-Wenzel state transition.